2006
DOI: 10.1007/bf03349215
|View full text |Cite
|
Sign up to set email alerts
|

Osteosarcoma and acromegaly: A case report and review of the litereture

Abstract: A 72-yr-old acromegalic man, who presented with pain in the left femur, was found to have a metastatic osteosarcoma. Only three cases describing the coexistence of acromegaly and osteosarcoma have been reported by the literature. As the patient didn't have other risk factors for osteosarcoma, the hypothesis that accelerated rate of bone turnover caused by long-term exposure to high GH and IGF-I could act as a predisposing factor in the development of this malignant bone tumor is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 41 publications
1
10
0
1
Order By: Relevance
“…Buckley found no consistent relation with height in a case-control study of 152 children with osteosarcoma [23], while Gelberg found a significant positive association with height one year before diagnosis [24]. Adult patients with acromegaly have been reported to be subject to osteosarcoma [25]. In our series, one child was treated with growth hormone (GH) for 3 years before diagnosis, following intrauterine growth retardation and a polymalformative syndrome, without biological GH deficiency.…”
Section: Discussionmentioning
confidence: 84%
“…Buckley found no consistent relation with height in a case-control study of 152 children with osteosarcoma [23], while Gelberg found a significant positive association with height one year before diagnosis [24]. Adult patients with acromegaly have been reported to be subject to osteosarcoma [25]. In our series, one child was treated with growth hormone (GH) for 3 years before diagnosis, following intrauterine growth retardation and a polymalformative syndrome, without biological GH deficiency.…”
Section: Discussionmentioning
confidence: 84%
“…Similarly scattered case reports exist describing various tumors including brain tumors [112][113][114], osseous tumors [115], skin epidermoid tumors and melanomas [116], adrenal tumors [117][118][119][120], and different lymphohematopietic neoplasms (lymphoma, multiple myeloma, chronic myeloid or lymphocytic leukemia) [121][122][123].…”
Section: Other Tumorsmentioning
confidence: 96%
“…The role of growth factors and osteosarcoma is further supported by case reports of osteosarcoma occurring in individuals with acromegaly (14). It is possible that subtle variations in genes that regulate growth, such as those in the growth hormone or the insulin-like growth factor (IGF) pathways, could lead to changes in cellular signaling, altered growth, and increased risk of tumorigenesis.…”
Section: Introductionmentioning
confidence: 97%